Anti-Jewish violence : rethinking the pogrom in East European history - Dekel-Chen, Jonathan L. (Indiana University Press, 2010)
Although overshadowed in historical memory by the Holocaust, the anti-Jewish pogroms of the late 19th and early 20th centuries were at the time unrivaled episodes of ethnic violence. Incorporating newly available primary sources, this collection of groundbreaking essays by researchers from Europe, the United States, and Israel investigates the phenomenon of anti-Jewish violence, the local and transnational responses to pogroms, and instances where violence was averted.